Lures for red palm weevil trapping systems: aggregation pheromone and synthetic kairomone. Issue 1 (9th May 2016) - Vacas, Sandra; Melita, Ourania; Michaelakis, Antonios; Milonas, Panagiotis; Minuz, Roxana; Riolo, Paola; Abbass, Mohamed Kamal; Lo Bue, Paolo; Colazza, Stefano; Peri, Ezio; Soroker, Victoria; Livne, Yaara; et al.
Abstract: BACKGROUND: The optimisation of the lure is essential for the implementation of trapping systems to control insect pests. In this work, the response of the red palm weevil (RPW), Rhynchophorus ferrugineus Olivier, to increasing emission rates of its aggregation pheromone (ferrugineol) and the efficacy of a convenient synthetic kairomone based on fermentation odours (ethyl acetate and ethanol) have been evaluated in different years and locations along the Mediterranean basin. RESULTS: In general, although capture data and emission had noticeable variability among locations, significantly fewer RPW were captured in pyramidal Picusan® traps with the lowest ferrugineol emission rates tested (0.6–3.8 mg day −1 ). Captures increased rapidly with ferrugineol emission up to 4–5 mg day −1 ; then, higher emission rates did not improve or reduce captures, up to the highest emission rate tested of 50.9 mg day −1 . Thus, there is no evidence of an optimum release rate corresponding to a maximum of RPW catches. Traps baited with the synthetic kairomone (1:3 ethyl acetate/ethanol) captured 1.4–2.2 times more total weevils than traps baited only with ferrugineol. Moreover, in most of the locations, the synthetic blend was at least as effective as the local coattractants used (plant material + molasses). CONCLUSIONS: Ferrugineol emission rate can vary in a wide range without significantly affecting RPW response. Coattractants based on fermenting compounds, ethyl acetate and ethanol, are able to improve the attractant level of ferrugineol and could be employed to replace non‐standardised natural kairomones in RPW trapping systems after further optimisation of their proportions and doses. © 2016 Society of Chemical Industry